2022
DOI: 10.1021/acs.iecr.2c02004
|View full text |Cite
|
Sign up to set email alerts
|

Application of Renormalization Corrections to SAFT-VR Mie

Abstract: SAFT-VR Mie is an established equation of state that offers excellent holistic descriptions of fluid behavior. However, the model does not account for the long-wavelength density fluctuations encountered in the critical region and can therefore not describe this region accurately. To this end, SAFT-VR Mie is treated with renormalization corrections, yielding SAFT-VR Mie + RG. This procedure is based on the ideas of White [J. Chem. Phys.199911193529356; J. Chem. Phys.200011232363244; J. Chem. Phys.2000113158015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 163 publications
0
5
0
Order By: Relevance
“…Therefore, it is not a result of the divergence of the heat capacity in the near-critical region but rather arises because of the formation of cyclic dimers. One can observe that the SAFT-VR Mie DBD model slightly overestimates the critical temperatures of the pure component as this is a classical equation of state, but crossover , or renormalization group approaches could improve the description of the data in the near-critical region. A significant underestimation of the liquid heat capacity of acetic acid is observed (Table , average absolute deviation (AAD) = 19%).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is not a result of the divergence of the heat capacity in the near-critical region but rather arises because of the formation of cyclic dimers. One can observe that the SAFT-VR Mie DBD model slightly overestimates the critical temperatures of the pure component as this is a classical equation of state, but crossover , or renormalization group approaches could improve the description of the data in the near-critical region. A significant underestimation of the liquid heat capacity of acetic acid is observed (Table , average absolute deviation (AAD) = 19%).…”
Section: Resultsmentioning
confidence: 99%
“…Models that are designed to pass through the experimental critical point, such as cubic EoSs or the CP-PC-SAFT, can better describe the vaporization enthalpy. In future studies, we plan to address this issue by using a crossover approach or by combining the renormalization group theory with the M-SAFT-VR Mie model. , …”
Section: Resultsmentioning
confidence: 99%
“…In future studies, we plan to address this issue by using a crossover approach or by combining the renormalization group theory with the M-SAFT-VR Mie model. 72,73 The values of repulsive stiffness (λ r ) obtained for refrigerants (Table 2) are generally much higher than the Lennard-Jones value of 12. The parameter λ r is particularly useful in describing derivative properties such as heat capacities and speeds of sound, as shown by Lafitte et al 15 The predictions of Joule−Thomson coefficients, as shown in Figure 11, are excellent, even though these data were not considered in the objective function.…”
Section: Halogenated Refrigerantsmentioning
confidence: 94%
“…Efforts to mitigate this issue have led to the introduction of so-called crossover approaches in SAFT-type EOSs. [16][17][18][19][20] While these methods are effective, they come at the cost of additional parameters and heightened computational complexity. Given these complications, such approaches appear less favorable for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…This overestimation subsequently results in imprecise representations of phase behavior close to the critical point. Efforts to mitigate this issue have led to the introduction of so‐called crossover approaches in SAFT‐type EOSs 16–20 . While these methods are effective, they come at the cost of additional parameters and heightened computational complexity.…”
Section: Introductionmentioning
confidence: 99%